Daughters of Miriam : women prophets in ancient Israel - Gafney, Wilda, 1966- (Fortress Press, 2008)
There are untold numbers of female prophets hiding in the masculine grammar and androcentric focus of the Hebrew scriptures. There are women-prophets in the communities around biblical Israel, existing for hundreds of years and even a thousand years before the Israelite and Judean prophets recorded their messages. The rabbinic and Christian fathers analyzed and found more women in the scriptures who function as prophets than the biblical authors identify. All of these female prophets have an intimate connection with the God of Israel; they express that connection by singing, dancing, drumming, speaking with and for God, waging war, performing miracles, exercising statecraft, and giving birth. Each of them is a daughter of Miriam, the mother of all women-prophets.Women prophets gave powerful voice to Yahwist faith at theformative moments in ancient Israel's development, and wereexpected in biblical visions of the future. Now they come to theforeground as Wilda C. Gafney explores prophetic practices inancient Israel, different models for women's sacred roles in the NearEastern environment, and changing understandings of women'sleadership in early and rabbinic Judaism as well.